Penerapan Language Experience Approach dalam Meningkatkan Keterampilan Membaca Siswa di Kelas Rendah - Lena, Mai Sri; Sartono, Sartono; Rafika, Rafika; Prameswari, Adiva Ayodia (MASALIQ, 2023)
Language Experience Approch is an approach to learning to improve elementary school students' reading skills. This study aims to determine the extent to which the Language Experience Approach (LEA) approach improves students' reading skills in lower grades. This research was conducted at SDN 01 Ladang Cakiah. The research uses a qualitative approach with interview techniques as a data collection tool. The research sample consisted of elementary school teachers who teach in lower grades. The results of the data analysis show that the students' experiences in learning with the LEA approach are very positive. Teachers revealed that learning with the LEA approach made them more interested in reading because they were given the opportunity to use their own language in learning. In addition, learning with the LEA approach encourages active participation of students in learning. This study shows that the LEA approach is very effective in improving students' reading skills in lower grades. Therefore, the LEA approach can be used as an effective alternative learning method in improving students' reading skills in low grades.